Athletes' involvement in decision making for good governence in sport - Grigaliunaite, I.; Eimontas, E. (Baltic Journal of Sport and Health Sciences, 2018)
Background. Governance is a key component of the effective organization management (Yeh & Taylor, 2008). Therefore, more and more researchers focus on good governance issues. The Initiative - Action for Good Governance in International Sports Organizations (AGGIS) set down guidelines for good governance, incorporating democratization processes. One of the growing good governance and its democratization concerns is involvement of stakeholders, in this case - athletes. Although governance decisions usually affect athletes directly, they have relatively low decision making power (Thibault, Kihl, & Babiak, 2010). The aim of this research was to highlight and discuss the importance of athletes` involvement in decision-making. Methods. Literature analysis was used to study athletes` role in organizational decision making and its evolvement in recent years. Theoretical framework allowed creating a survey with a purpose to assess the current situation in national sports federations. Results and conclusions. Literature analysis revealed increasing democratization within sport organizations, which affects greater involvement of athletes in decision making. Theoretical framework allowed making recommendations for sports organizations so that they could become more athlete-centred. Although increasing democratization resulted in greater athletes` involvement in decisions making, some issues still remain unresolved.